2015
DOI: 10.1017/ice.2014.9
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Staff Behavior on Infectious Risk in Operating Rooms: What Is the Evidence?

Abstract: SUMMARY A systematic literature review was performed to assess the impact of surgical-staff behaviors on the risk of surgical site infections. Published data are limited, heterogeneous, and weakened by several methodological flaws, underlying the need for more studies with accurate tools. OBJECTIVE To assess the current literature regarding the impact of surgical-staff behaviors on the risk of surgical-site infection (SSI). DESIGN Systematic literature review. METHODS We searched the Medline, EMBASE, Ovid, Web… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
50
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(55 citation statements)
references
References 47 publications
(132 reference statements)
2
50
0
3
Order By: Relevance
“…Also, the doors of an OR must be closed as much as possible, because every time the door opens, the pressure drops and turbulence in air movements occur, contributing to wound contamination [80]. To reduce the frequency of door openings, Birgand et al suggest a more practical storage of frequently used materials, advanced communication systems and an improved organisation of surgical team shift changes [79,82].…”
Section: Operative Environmentmentioning
confidence: 99%
“…Also, the doors of an OR must be closed as much as possible, because every time the door opens, the pressure drops and turbulence in air movements occur, contributing to wound contamination [80]. To reduce the frequency of door openings, Birgand et al suggest a more practical storage of frequently used materials, advanced communication systems and an improved organisation of surgical team shift changes [79,82].…”
Section: Operative Environmentmentioning
confidence: 99%
“…In a literature review, Birgand et al 33 reported that in two studies, the number of personnel in the OR and SSI rates or airborne contaminants were correlated; they also reported that in an additional three studies, door openings and airborne contaminants were linked. Reducing traffic and door openings, especially involving the main door, may be a practical solution to maintaining optimal airflow with minimal circulating particles and contaminants; however, data were limited, and the level of evidence was low 33 .…”
Section: Airborne Sources and Control Of Contaminantsmentioning
confidence: 99%
“…In a literature review, Birgand et al 33 reported that in two studies, the number of personnel in the OR and SSI rates or airborne contaminants were correlated; they also reported that in an additional three studies, door openings and airborne contaminants were linked. Reducing traffic and door openings, especially involving the main door, may be a practical solution to maintaining optimal airflow with minimal circulating particles and contaminants; however, data were limited, and the level of evidence was low 33 . Esser et al 34 counted the number of OR door openings before and after developing a policy that included staff member education, reminder signs on OR doors, and use of communication devices such as voice‐activated phones to minimize the need to leave the OR for supplies or instruments.…”
Section: Airborne Sources and Control Of Contaminantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Operating room traffic is often associated with transitions of care and handoffs, which are believed to contribute to adverse patient outcomes [27][28][29][30][31][32], including infection [33]. It is unclear whether operating room traffic in general or the traffic of specific personnel groups impacts SSI risk [34].…”
mentioning
confidence: 99%